Chondroid lipoma of the thigh: A case report - Parasappa Joteppa Yaranal; Vijayakumar Hegde (Wolters Kluwer Medknow Publications, 2013)
Chondroid lipoma is an unusual, unique benign lipomatous tumor. We present a case of chondroid lipoma of right thigh in 46-year- old female to highlight the distinct morphological simily, it is important to distinguish it from extraskeletal chondrosarcoma and myxoid liposarcoma. The review of the literature has been discussed.